2023
DOI: 10.3389/fvets.2023.1170573
|View full text |Cite
|
Sign up to set email alerts
|

Low-protein diets supplemented with glycine improves pig growth performance and meat quality: An untargeted metabolomic analysis

Abstract: For the purpose to improve meat quality, pigs were fed a normal diet (ND), a low protein diet (LPD) and a LPD supplemented with glycine (LPDG). Chemical and metabolomic analyses showed that LPD increased IMF deposition and the activities of GPa and PK, but decreased glycogen content, the activities of CS and CcO, and the abundance of acetyl-CoA, tyrosine and its metabolites in muscle. LPDG promoted muscle fiber transition from type II to type I, increased the synthesis of multiple nonessential amino acids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In addition to effective response to selective breeding 35 , this elevated IMF level is explained by research experimental conditions, including the diet. Current diets are at least 3% lower in protein than previous ones 5 and reduced protein diets increase IMF 39,50 . This, in combination with high nutrient intake during growth, could have increased the number and size of adipocytes in skeletal muscle 51,52 and blurred the effect of LEPR on IMF, particularly in LM, GM and ST. Leptin gene expression differs across adipose depots, marking especially subcutaneous fat 53 .…”
Section: Discussionmentioning
confidence: 95%
“…In addition to effective response to selective breeding 35 , this elevated IMF level is explained by research experimental conditions, including the diet. Current diets are at least 3% lower in protein than previous ones 5 and reduced protein diets increase IMF 39,50 . This, in combination with high nutrient intake during growth, could have increased the number and size of adipocytes in skeletal muscle 51,52 and blurred the effect of LEPR on IMF, particularly in LM, GM and ST. Leptin gene expression differs across adipose depots, marking especially subcutaneous fat 53 .…”
Section: Discussionmentioning
confidence: 95%
“…conducted RNA immunoprecipitation sequencing (MeRIP-seq) and RNA sequencing (RNA-seq) analyses on breast and leg tissues from 180-day-old Jingyuan chickens, revealing differentially methylated genes involved in the regulation of muscle lipid anabolism, including enoyl-CoA hydratase 1 (ECH1), branched chain amino acid transaminase 1 (BCAT1), and cytochrome P450 family 1 subfamily B member 1 (CYP1B1) [83]. Yu et al (2023) demonstrated that the m 6 A-induced ferroptosis pathway in breast muscle tissue was a novel target for regulating IMF metabolism and validated the finding that chicken Leiomodin 2 (LMOD2) and its multiple m 6 A negative regulatory DMGs are potential regulators of differential IMF deposition in muscle [84]. These provided an important theoretical basis for exploring the functional mechanism of m 6 A in IMF deposition in chickens.…”
Section: Epigenetic Modificators Controlling Imf Depositionmentioning
confidence: 91%
“…Feng et al (2021) constructed a glucocorticoid receptor (GR)-mediated corticosterone-induced fatty liver syndrome (FLS) model in chickens and found that hepatic lipid accumulation was increased in laying hens fed a low-protein (HELP) diet (p < 0.05), which may be caused by specific clearance of m 6 A modifications of FASN, SREBP1, and SCD lipogenesis-related genes [81]. Li et al (2022) used different doses of methyl donor betaine and methylation inhibitor cycloleucine to treat chicken primary preadipocytes and found that m 6 A modification was negatively correlated with chicken preadipocyte production and FTO through demethylation. Chemically regulates the expression of CTNNBI, thereby promoting adipogenesis [82].…”
Section: Epigenetic Modificators Controlling Imf Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 mg of powdered sample were added with 500 μL of extraction solution (MeOH:ACN:H 2 O, 2:2:1, v/v) containing isotope labeled internal standards, sonicated on ice, and centrifuged at 13,800×g, 4°C for 15 min. The supernatants was collected and passed through a 0.22 μm filter before used for liquid chromatographic tandem mass spectrometric (LC-MS/MS) analysis [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%